48 Chyle Leak Following Pancreaticoduodenectomy: A Tertiary HPB Unit 14-year Experience and a Proposed Management Algorithm. (4th May 2021) - Russell, T; Tanase, A; Aroori, S
Abstract: Introduction: Chyle leak (CL) is an uncommon complication of pancreaticoduodenectomy (PD). Its incidence, risk factors, and effect on prognosis are not well described and optimum management remains debated. This study aims to calculate the incidence of CL, identify risk factors, consider effect on patient outcome, and propose a simple management algorithm. Method: This is a retrospective review of all patients who developed CL following PD between January 2006 and April 2020. The following details were obtained from a prospectively maintained database: age, ASA grade, BMI, details of operation, tumour histology, length of stay, and mortality. Results: A total of 560 patients underwent PD and 17 (3.04%) developed CL. These patients had significantly higher BMI (P < 0.01) and significantly longer operation times (P < 0.05). CL patients had a higher rate of portal vein (PV) tumour adherence, PV resection, and intra-operative blood transfusion although this was not statistically significant. Sixteen CL patients (94.1%) were managed successfully with a non-operative approach. Conclusions: 3.04% of patients who underwent PD developed CL. CL was associated with higher BMI and longer operation time. CL did not affect length of stay. The vast majority of CL cases can be managed successfully with a non-operative approach.